Husserl's missing technologies - Ihde, Don, 1934- (Perspectives in continental philosophy., 2016)
Don Ihde, contemporary postphenomenological philosopher of science and technology--technoscience--examines the important philosophical role of Husserl, here in relation to technologies, and his classical phenomenology. With concrete analyses of both the science of Husserl's time and a retrospective reading from new technoscience interpretations, scientific instruments, technologies of reading and writing, and new imaging technologies are discussed.